Protective effects of vitamin E on carbon tetrachloride-induced liver damage in rats - Naziroglu, M; Çay, M; Üstündag, B; Aksakal, M; Yekeler, H (Wiley, 1999)
In this study we investigated whether the increase of hepatic vitamin E content by intraperitoneal administration, influences chronic liver damage induced by carbon tetrachloride (CCl4) in rats. Thirty adult male Wistar rats were divided into three groups. The first group was used as a control and the rats in the second group were administered CCl4 in olive oil subcutaneously. Rats in the third group were administered intraperitoneally vitamin E (dl-alpha-tocopherol acetate, 100 mg kg(-1)). This administration was performed three times per week for five weeks. Liver samples were used for the determination of vitamin E levels, glutathione peroxidase (GSHPx) activities and histological examination. Serum levels of alanine aminotransferase, lactate dehydrogenase, alkaline phosphatase, aspartate amino transferase, gamma-glutamyltranspeptidase, total and conjugated bilirubin were significantly (p < 005, p < 0.01, p < 0.001) higher in animals treated with CCl4 than in the controls and had returned to normal values by the administration of vitamin E + CCl4. Liver vitamin E levels were significantly (p < 0.05) lower in the CCl4 group than in he control group. However, the liver vitamin E content was significantly (p < 0.01, p < 0.001) increased in the vitamin E + CCl4 injected group. On the other hand, liver GSHPx activity was not statistically different among the groups. On histological examination, vitamin E administered animals showed incomplete, but significant, prevention of liver necrosis and cirrhosis induced by CCl4. these data indicate that intraperitoneally administered vitamin E has protective effects against CCl4-induced chronic liver damage and cirrhosis as evidenced by biochemical data and conventional histological examination. Copyright (C) 1999 John Wiley & Sons, Ltd.
Keywords: vitamin E; glutathione peroxidase; cirrhosis; liver damage; CCl4; free radicals; biochemical and haematological parameters; rat